SOCIODEMOGRAPHIC, KNOWLEDGE AND ATTITUDE TOWARD COVID-19 PREVENTION MEASURE IN GIRI AGUNG VILLAGE, EAST KALIMANTAN, INDONESIA: A CROSS-SECTIONAL STUDY - Sulistyawati, Sulistyawati; Mustanginah, Tri; Maulana, Muchsin (The Indonesian Journal of Public Health, 2024)
Introduction: In mid-2022, a Central Statistics Agency (BPS) survey reported that Indonesian people's compliance with COVID-19 prevention measures ranged between 70-84%. Many studies have also measured preventive behavior in urban areas but are still limited to rural areas. The information exposure of rural communities can be much different from that of urban communities, facilitated by technological developments. Aims: This research looked at COVID-19 prevention behavior in rural settings, which is essential to support targeted prevention programs. Methods: This study employed a quantitative study design with an analytical observational design through a cross-sectional approach. Residents aged 17 to 55 were recruited in Giri Agung Village, Sebulu, Kutai Kartanegara, East Kalimantan. Chi-square and Binary Logistic Regression were used to analyze the data. Result: This research found a significant association between gender (p-value=0.002), education (p-value=0.003), knowledge (p-value=0.008), and attitudes (p-value=0.001) toward COVID-19 prevention measures. We discovered that education level most influenced prevention measures in binary logistic regression. Conclusions: Knowledge is one of the most critical factors in realizing action because it can build trust to perceive reality, make decisions, and determine actions to be taken on an object